Efisiensi Penggunaan Quick Response Code Indonesia Standart (Qris) Terhadap Peningkatan Penjualan Pada Umkm Di Le Garden Palembang Indah Mall - Amir Salim Salim; Doly Nopiansyah (UNIVED Press, 2023)
The quick development of technology and information across a range of digital platforms, marketplaces, and markets gives SMEs a place to promote their goods and contact customers in different parts of Indonesia and overseas. Bank Indonesia and the Indonesian Payment System Association (ASPI) continue to develop and upgrade the QRIS payment system in order to maximize the efficiency of non-cash payment system services in the digital age. This study aims to ascertain the usage of Quick Response Code Indonesia Standard (QRIS) in boosting sales to MSMEs at Le Garden Palembang Indah Mall and to assess the efficiency of QRIS usage in boosting MSMEs sales at Le Garden Palembang Indah Mall. (1) Observation, interviews, and documentation are all used in this study's qualitative data gathering methods. At Le Garden Palembang Indah Mall, 38 SMEs in total participated in the study. using inadvertent sampling and saturated sampling approaches to identify informants. Based on the findings of the study, (1) the practice of using Quick Response Code Indonesia (QRIS) to increase sales to MSMEs at Le Garden Palembang Indah Mall starts with the customer informing the employee that they would like to make a non-cash payment. The customer is then directed to scan the QR Code and type in the nominal amount to be paid, after which the customer's balance will automatically decrease. (2) Measurement of outcomes (output) and input refers to the effectiveness of employing Quick Response Code Indonesia (QRIS) on boosting sales to MSMEs at Le Garden Palembang Indah Mall. Transactions take less time, are simpler, and are more effective for those who accept the presence of QRIS.